Dancing is the best medicine : the science of how moving to a beat is good for body, brain, and soul - Christensen, Julia F.; Chang, Dong-Seon (Greystone Books, 2021)
"We've all explored dance at some point in our lives--in a class, at a wedding, or at a club, crammed onto the floor and moving with the music. But dance is much more than a pleasurable way to pass the time. It could very well be the secret to a happy and healthy life. In Dancing Is the Best Medicine, Julia F. Christensen and Dong-Seon Chang--neuroscientists by day and dancers by night--explore why dancing is good for the body, mind, and soul. Movement, they explain, keeps us healthy, and dance in particular benefits posture, coordination, balance, and fitness. It can be as effective for our cardiovascular health as extreme exercise yet can also be safely practiced by heart attack and stroke patients. It helps with diabetes, arthritis, back pain, and Parkinson's, reduces inflammation, helps to control weight, and improves our immune system. Dancing also makes us happy; it lowers cortisol levels and releases feel-good neurotransmitters and hormones. Best of all, dancing is for everyone. Young or old, physically fit or recovering from an injury, healthy or coping with a chronic illness, there's a dance out there that's perfect for you. So what are you waiting for? Follow Christensen and Chang's lead and get out there and dance!"--